Sistem Pengendalian Water Pump Untuk Mengatur Volume Level Air Dengan Logika Fuzzy Pada Pengairan Hidroponik - Kurniawan, Rakhmat; Sriani, S; Ramadhan, Alfan (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
Hydroponic culture can produce optimal plant growth, the yield and quality are better than soil media, the efficiency and quality of production depends on many factors such as controlling nutrition, plant genotype, freezing method, disease control, temperature control and controlling the amount of water in the tendons. Water that is circulated through the hydroponic network is supplied through a water pump. A lot of water supply cannot be stable, which can result in a decrease in plant quality, namely the control of hydroponic water pumps can be adjusted with the Tsukamoto fuzzy system. This study used the NFT hydroponic method, which is suitable for green vegetables such as mustard greens, lettuce, spinach, pakcoy, cucumber, tomatoes, and others. The application of this pump sensor monitoring tool uses a microcontroller based on the IoT platform. Also used Blynk software to display information from programming via Arduino software. Ultrasonic circuit, the sensor will measure the distance to the air surface, which will determine at what distance the water tap will open to fill air into the tendons. After running a number of experiments the content of water tendons can be controlled by fuzzy Tsukamoto. It is hoped that for further development it can use sensors other than Ultrasonic, and for further development it can use a large number of plants.